Impact of advance care planning on the care of patients with heart failure: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Malhotra, Chetna; Sim, David; Jaufeerally, Fazlur; Vikas, Nivedita; Sim, Genevieve; Tan, Boon; Ng, Clarice; Tho, Pei; Lim, Jingfen; Chuang, Claire; Fong, Florence; Liu, Joy; et al.
Abstract Background Despite the promise and popularity of advance care planning, there is insufficient evidence that advance care planning helps patients to meet their end-of-life care preferences, especially in Asian settings. Thus, the proposed study aims to assess whether patients with advanced heart failure who are receiving advance care planning have a greater likelihood of receiving end-of-life care consistent with their preferences compared to patients receiving usual care. Secondary objectives are to compare differences in health care expenditures, quality of life, anxiety and depression, understanding of own illness, participation in decision-making and concordance with their caregiver's preferences for end-of-life care, between patients with advanced heart failure receiving advance care planning and usual care. Methods/design This is a two-arm randomized controlled trial of advance care planning versus usual care (control) conducted at two institutions in Singapore. Two hundred and eighty-two patients with advanced heart failure (n = 94 in the advance care planning arm;n = 188 in the control arm receiving usual care) will be recruited from these centers and followed for 1 year or until they die, whichever is earlier. Additionally, the study will include up to one caregiver per patient enrolled. Discussion If advance care planning is proven to be effective, the results will help to promote its uptake among health care providers and patients both within Singapore and in other countries. Trial registration NCT02299180 . Registered on 18 November 2014.